DEFINING PRIVATE PROPERTY INTERESTS IN AMERICA’S NEW ECONOMIC REALITY: THE CASE FOR THE PRIMACY OF FEDERAL LAW IN TAKINGS LITIGATION - Allen, Laura E. (Journal of Law and Commerce, 2013)
DEFINING PRIVATE PROPERTY INTERESTS IN AMERICA’S NEW ECONOMIC REALITY: THE CASE FOR THE PRIMACY OF FEDERAL LAW IN TAKINGS LITIGATION